2015
DOI: 10.3109/09553002.2015.1068462
|View full text |Cite
|
Sign up to set email alerts
|

2.1 GHz electromagnetic field does not change contractility and intracellular Ca2+transients but decreases β-adrenergic responsiveness through nitric oxide signaling in rat ventricular myocytes

Abstract: Long-term exposure to 2.1 GHz EMF decreases β-AR responsiveness of ventricular myocytes through NO signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, the enhanced activity of voltage-gated calcium channels (VGCCs) have been delineated, after exposure to EMR in many cell types (94)(95)(96). Previous studies used the activity of VGCCs as an indicator of microwave radiation induced changes in ion channels (96,97). The level of neurotransmitters can indicate the membrane properties, such as the expression level of synaptic vesicular-associated proteins, can indicate the function of the synaptic vesicular membrane (22,98).…”
Section: Cell Membrane Damagementioning
confidence: 99%
“…Additionally, the enhanced activity of voltage-gated calcium channels (VGCCs) have been delineated, after exposure to EMR in many cell types (94)(95)(96). Previous studies used the activity of VGCCs as an indicator of microwave radiation induced changes in ion channels (96,97). The level of neurotransmitters can indicate the membrane properties, such as the expression level of synaptic vesicular-associated proteins, can indicate the function of the synaptic vesicular membrane (22,98).…”
Section: Cell Membrane Damagementioning
confidence: 99%
“…Olgar et al found that EMF of 2.1 GHz does not change the contractility and intracellular Ca2+ transients but decreases β-adrenergic responsiveness through NO signaling in rat ventricular myocytes while EMF exposure led to a signifi cant increase in NO levels in rat heart (47). A study by Zhu et al, showed that an exposition to 2450 MHz for 20 min caused an edema in myocardial cells, malalignment in muscle fi bers, obvious injury in cells, and signifi cant increase in expression of Caspase-3 and HSP 70 protein in EMR group (48).…”
Section: Tab 3 the Effects Of Melatonin And 2450 Mhz Emr On Malondimentioning
confidence: 99%